No improvement of repeated-sprint performance with dietary nitrate - Martin, K.; Smee, D.; Thompson, K. G.; Rattray, B. (International Journal of Sports Physiology and Performance, 2014)
PURPOSE: Nitrate supplementation improves endurance exercise and single bouts of high-intensity activity, but its effect on repeated sprints is unclear. This study is the first to investigate the effects of acute dietary nitrate supplementation during a high-intensity intermittent-sprint test to exhaustion. METHODS: Team-sport athletes (9 male, age 22.3 ± 2.1 y, VO2max 57.4 ± 8.5 mL /kg·min; 7 female, age 20.7 ± 1.3 y, VO2max 47.2 ± 8.5 mL/kg· min) were assigned to a double-blind, randomized, crossover design. Participants consumed 70 mL of concentrated beetroot juice containing a minimum of 0.3 g of nitrate (NT) or 70 mL of placebo (PL) 2 h before a repeated-sprint protocol involving repeated 8-s sprints with 30-s recovery on a cycle ergometer to exhaustion. RESULTS: Fewer sprints (NT = 13 ± 5 vs PL = 15 ± 6, P = .005, d = 0.41) and less total work (NT = 49.2 ± 24.2 kJ vs PL = 57.8 ± 34.0 kJ, P = .027, d = 0.3) were completed in NT relative to PL. However there was no difference in overall mean power output or the mean power output for each individual 8-s sprint. CONCLUSIONS: These findings suggest that dietary nitrate is not beneficial for improving repeated-sprint performance, at least when such sprints are near-maximal and frequent in nature. The lack of an effect of nitrate at near-maximal oxygen uptake supports the suggestion that at greater exercise intensities nitrate does not have an ergogenic effect.